2021
DOI: 10.1053/j.jvca.2020.08.041
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Asymptomatic Pre-Surgical Population for Severe Acute Respiratory Syndrome Coronavirus 2

Abstract: IN RESPONSE to the coronavirus disease 2019 (COVID-19) pandemic, healthcare facilities deferred all but emergency surgeries for 12 weeks to minimize/reduce risk to patients and healthcare workers. 1-6 However, by April 2020, increased mortality for delaying necessary cardiac and thoracic procedures prompted multidisciplinary teams to determine how to restart surgical cases safely, balancing the urgent needs of patients, the reported increased morbidity and mortality of COVID-19Àpositive patients undergoing sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…A comparable study tested 36 939 patients over 14 weeks for all surgical specialties and found an overall positivity rate of 5.71%. 9 This positivity rate varied significantly in symptomatic (7.0%) and asymptomatic (0.41%) individuals. Dalvin et al 10 focused on presurgical testing in ophthalmic patients and found that 7 (0.60%) of 1173 patients tested positive for COVID-19 via PCR in presurgical screening.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…A comparable study tested 36 939 patients over 14 weeks for all surgical specialties and found an overall positivity rate of 5.71%. 9 This positivity rate varied significantly in symptomatic (7.0%) and asymptomatic (0.41%) individuals. Dalvin et al 10 focused on presurgical testing in ophthalmic patients and found that 7 (0.60%) of 1173 patients tested positive for COVID-19 via PCR in presurgical screening.…”
Section: Discussionmentioning
confidence: 94%
“…Given the low positivity rates as well as the low positivity rates seen in asymptomatic patients at other institutions, universal presurgical COVID-19 testing of all patients can be viewed as a costly, low-yield exercise. 9 , 10 Even with a positive test result, most patients underwent their procedure as scheduled, generally indicating that a positive result does not affect the original surgical plan. Considering the resources needed to mitigate the spread of COVID-19 (ie, masks for all parties, sanitation supplies, time to clean rooms) and the significant decrease in procedures seen during the pandemic, this represents another added cost to the healthcare system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation